Kreatifitas Gerak Melalui Proses Imajinasi dan Intuisi dalam Bentuk Koreografi - Nursyam, Romi; Cahyadi, Ojang; Suwandi, Tuteng (Jurnal Pendidikan Tari, 2023)
The aim of this research is to find out how students develop their creativity, how students develop their imagination and intuition, and how students carry out creative movement activities through imagination and intuition into dance works. This research uses a descriptive method, examining the data that has been collected. The research method used is based on the problem to be solved, starting with a study of the development of Dance Program students' choreography using naturalistic qualitative methods. This research is expected to produce a form of learning from the teaching and learning process to the form of innovative dance works. The results of the research are a description of the students' creative process in creating movement through Imagination and Intuition processes. The research lasted 6 months, from March to October 2017.